Developing just transition pathways for Africa’s agriculture towards low emission and climate resilient development under a 1.5°C global warming - Mapfumo, P.; Rurinda, J.; Cramer, Laura K.; Mushore, T.D.; Wamukoya, George (CAB International, 2025)
Novel climate conditions are posing a serious threat to humanity and ecological systems, presenting and aggravating social injustices at different levels. African agriculture-based livelihood systems will be invariably the most affected because of their reliance on climate-sensitive agriculture and limited adaptive capacity due to low economic development linked primarily to historical contingency. Just transition pathways for Africa’s agriculture are urgently required for sustainable production systems that enhance food security and poverty reduction, while optimising mitigation co-benefits. We critically reviewed and synthesised literature from relevant scientific reports and peer-reviewed articles to develop a framework for just transition pathways for Africa’s agriculture towards low emission and climate resilient development under a 1.5°C global warming. We first characterise current and future climate hazards and assess climate risks underpinning African agriculture-based livelihoods. Our results demonstrated that a 1.5°C global warming will be approached by 2040 in all five subregions of Africa, even under low emission scenarios. This is despite Africa emitting <4% concentration of greenhouse gas emissions in the atmosphere. The African agriculture-based livelihood systems have experienced considerable losses and damages from climate change and this will worsen with increasing intensity of climate hazards. Neither the existing or planned incremental adaptation mechanisms nor the anticipated benefits of mitigatory measures are sufficiently comprehensive to match the pending novel climate conditions. We argue that the just transition pathways for Africa’s agriculture should be anchored on reprogramming of the cropping, livestock and fishery systems for climate-proofing with a specific focus on the following underpinnings: financing the advancement of science, technology and innovation; restoring neglected or underulitised crops and livestock genetic pools; regenerating soil fertility and advancing soil health; restoring degraded land; protecting natural ecosystems and biodiversity; accessing quality education training and information technologies; and developing markets and creating novel distribution and trade opportunities. Such efforts should also focus on mechanising and greening Africa’s agriculture as driven by a deliberate ‘Green Industrial Revolution’ for the new normal induced by climate change. The sustainability of climate change response and a just transition pathway framework for Africa also lies in the corresponding transformation of education systems and research capacities tailored to drive economic development for Africa. In conclusion, the developed just transition framework offers opportunities for social inclusion, equity, building capacity for self-mobilisation and self-organisation of communities for climate action, and investments in the transition pathways for building a climate resilient agriculture towards zero poverty and meaningful contribution towards zero carbon.